2014
DOI: 10.1007/s00248-014-0485-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on Tribological Mechanism for Multi-layer Porous Structure of Diatom Frustule

Abstract: Tribological mechanism of the diatom frustule with multi-layers of pores is studied with the liquid-solid interaction (FSI) method. Based on the reconstructed representative Coscinodiscus sp. frustule with two-layer porous structure, the tribological performances for the diatom frustule at its different pore diameter ratios, pore depth ratios, and velocities are solved through governing equations involved with FSI method. The numerical result shows that the existence of the two-layer porous structure of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recently, the first author of the present paper and co-workers pointed out that the compound texture with two-layer pores can more effectively improve the frictional behaviors of the tribological pair, compared with the single-layer texture. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the first author of the present paper and co-workers pointed out that the compound texture with two-layer pores can more effectively improve the frictional behaviors of the tribological pair, compared with the single-layer texture. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first author of the present paper and co-workers pointed out that the compound texture with two-layer pores can more effectively improve the frictional behaviors of the tribological pair, compared with the singlelayer texture. 13,14 Under the high speed or heavy-duty condition, frictional noise occurs in the journal bearing. Although there exist some researches on the friction noise of the journal bearing caused by the surface roughness, wear debris, etc., [15][16][17] only little work about the noise of the compound textured bearing was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Meng et al. 1416 also found that the compound dimple, characterized by two-layer pores, can better improve the load-carrying capacity and reduce the friction of parallel surfaces in comparison to the simple dimple with only one-layer pore. Further, dimple effects on the tribological performances of journal bearings are also studied by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] By applying surface texturing to the piston ring of an engine, Meng et al 12,13 found that surface texturing can reduce the friction force and wear of the piston-ring system. Besides, Meng et al [14][15][16] also found that the compound dimple, characterized by two-layer pores, can better improve the load-carrying capacity and reduce the friction of parallel surfaces in comparison to the simple dimple with only one-layer pore. Further, dimple effects on the tribological performances of journal bearings are also studied by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In early 2015, the first author of the present work conducted some preliminary studies on tribological performance for surfaces with cylindrical-cylindrical and rectangular-spherical dimples. The author's result showed that the two types of dimples on the inner surface of the journal bearing can generate a larger load-carrying capacity and smaller friction coefficient in comparison with the one-layer dimple (Meng et al, 2015a(Meng et al, , 2015b. However, these research works are conducted for smooth bearing surfaces.…”
Section: Introductionmentioning
confidence: 99%